The Edukasi Pemanfaatan Obat Tradisional Untuk Meningkatkan Imunitas Tubuh” di Desa Sejahtera Kecamatan Palolo, Kabupaten Sigi, Sulawesi Tengah - Puspita Dewi, Niluh; insani, fadilah; Sujati, Ni Wayan; Astria Polontalo, Nani; lidia, lidia (Jurnal Mandala Pengabdian Masyarakat, 2024)
The use of traditional medicine in Indonesia is also related to the many types of plants in this country, understanding of traditional medicine is still very lacking so it is necessary to provide education about traditional medicine. The aim of carrying out this service is to provide understanding and skills to the people of Sejahtera Village about the use of traditional medicine to increase body immunity. This activity was attended by 40 people. The result of this activity was increased knowledge about the processing, types and use of traditional medicines. Counseling is provided using an interactive lecture method through distribution of leaflets, traditional medicine books and social service. The effectiveness of the extension was tested by administering a questionnaire on community satisfaction with the activities carried out. The results of service activities have provided increased knowledge and skills of the community regarding how to use traditional plants for body immunity.